Strategi Untuk Meningkatkan Mutu Pendidikan: Studi Kasus di SMK Al-Washliyah 13 Kota Tebing Tinggi - Bariqi Abhari Saragih; Irgi Fahreza; Lutfiah Azhar Nst; Suri Lestari Br. Purba (Universitas Muhammadiyah Enrekang, 2022)
Strategic management is a process of integrating planning, implementation and evaluation which leads to organizational decision making that has an impact on organizational excellence. Quality education can be implemented if schools implement the right strategic management to be implemented. The purpose of this study is to describe how strategic management is to improve the quality of education at SMK Al Washliyah 13, Tebing Tinggi City. This study uses descriptive qualitative methods and data collection techniques are interviews and observations. Strategies to improve the quality of education at SMK Al Washliyah 13 Tebing Tinggi City are through improving the quality of teachers, curriculum, increasing human resources, increasing student academic achievement, and building the image of the institution.